CRISPR‐Cas9 mediated OsMIR168a knockout reveals its pleiotropy in rice. Issue 2 (5th October 2021) - Zhou, Jianping; Zhang, Rui; Jia, Xinyu; Tang, Xu; Guo, Yachong; Yang, Han; Zheng, Xuelian; Qian, Qian; Qi, Yiping; Zhang, Yong
Summary: MicroRNA168 (MIR168) is a key miRNA that targets the main RNA‐induced silencing complex component Argonaute 1 (AGO1) to regulate plant growth and environmental stress responses. However, the regulatory functions of MIR168 need to be further elucidated in rice. In this paper, we generated clean OsMIR168a deletion mutants by CRISPR‐Cas9 strategy. We then phenotypically and molecularly characterized these mutants. The rice OsMIR168a mutants grew rapidly at the seedling stage, produced more tillers and matured early. Compared to the wild‐type plants, the mutants were shorter at maturity and produced smaller spikelets and seeds. Analysis of gene expression showed that the transcription levels of OsMIR168a 's target genes such as OsAGO1a, OsAGO1b and OsAGO1d were elevated significantly in the OsMIR168a mutants. Intriguingly, OsAGO18, a member of a new AGO clade that is conserved in monocots, was confirmed to be a target of OsMIR168a not only by informatic prediction but also by expression analysis and a cell‐based cleavage assay in the OsMIR168a mutants. Many protein‐coding g enes and miRNAs showed differential expression in the OsMIR168a mutants, suggesting OsMIR168a exerts a major transcriptional regulatory role, likely through its potential target genes such as OsAGO1s and OsAGO18 . KEGG enrichment analysis of these differentially expressed genes pointed to OsMIR168a 's involvement in important processes such as plant hormone signalling transduction and plant–pathogen interaction. These data collectively support that the complex regulation module of OsMIR168a ‐ OsAGO1 / OsAGO18 ‐ miRNA s‐target genes contributes to agronomically important traits, which sheds light on miRNA‐mediated crop breeding.